دور الذكاء الاستراتيجي في تطوير أداء شركات التأمين (دراسة ميدانية على شركات التأمين الخاصة في الساحل السوري( - قاسم سامر; كنعان علي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يتناول هذا البحث دور الذكاء الاستراتيجي في تطوير أداء شركات التأمين حيث يسهم الذكاء الاستراتيجي في مساعدة المنظمات بتحقيق أهدافها والتفاعل مع بيئتها بدرجة كبيرة من المرونة، من خلال ما يوفره لها من تنبؤات بالفرص والتهديدات المحيطة بها، واتخاذ الإجراءات المناسبة على أسس من المعرفة والتفكير المنظم؛ مما يمكن المنظمة من الاستجابة لتغيرات البيئة الحالية والمستقبلية، والتخطيط والتنبؤ بالنتائج مما ينعكس إيجاباً على الأداء. ويتكون الذكاء الاستراتيجي من عدة عناصر أهمها: الاستشراف، التفكير المنظم، الرؤية المستقبلية، الدافعية، والشراكة. يهدف البحث إلى تحليل واقع تطبيق عناصر الذكاء الاستراتيجي في شركات التأمين الخاصة في الساحل السوري، ودراسة طبيعة وقوّة العلاقة التي تربط بين الذكاء الاستراتيجي والأداء. ولتحقيق ذلك تمّ صياغة ثلاث فرضيّات، واستخدم الباحث أسلوب الاستبانة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample t. test، واختبار الارتباط الثّنائي Pearson Correlation، واختبار الانحدار المتعدد. وقد توصل الباحث إلى عدّة نتائج أهمّها: يتوافر الذكاء الاستراتيجي في الشركات المدروسة بتقييم متوسط، كما توجد علاقة طردية موجبة بين الذكاء الاستراتيجي والأداء، ويوجد علاقة ذات دلالة احصائية لعناصر الذكاء الاستراتيجي على الأداء في الشركات محل الدراسة باستثناء عنصري الرؤية المستقبلية والدافعية. This research deals with the role of strategic intelligence in the development of the performance of insurance companies where strategic intelligence contributes to helping organizations achieve their goals and interact with their environment with a great deal of flexibility, by providing them with predictions of opportunities and threats, and taking appropriate action on the basis of systematic knowledge and thinking, enabling the organization to respond to current and future environment changes, and planning and forecasting results, which reflected positively on performance, strategic intelligence consists of several elements, including: foresight, systematic thinking, future visioning, motivation, and partnership. The research aims to analyze the reality of applying the elements of strategic intelligence in Private Insurance Companies in The Syrian Coast, and study the nature and strength of the relationship between strategic intelligence and performance. To achieve this, three hypotheses were formulated. The researcher used the questionnaire method to collect the data and analyzed it by using statistical tests, the most important of which were: the one-sample T. test, the Pearson Correlation test, and the multiple regression test. The researcher found several results, the most important of which is: Strategic intelligence is available in the studied companies with an average evaluation. There is also a positive correlation between strategic intelligence and performance. There is a statistically significant effect on the elements of strategic intelligence on performance in the studied companies, except for the elements of future vision and motivation.